نظرية أفعال الكلام بين الدراسات الغربية والتراث العربي - نجاح, مدلل (جامعة الوادي - University of Eloued, 2021)
ملخص: إن كل متتبع للكتب والمصادر التي تناولت المنهج التداولي بالدراسة، يجدها لا تخلو من عرض لمبادئ نظرية الأفعال الكلامية ،ذلك أنها تعد قرينة التداولية، والملفت للنظر أن كل هذه الدراسات لها جذور أصيلة في تراثنا العربي الذي يتميز بالشمولية والموسوعية، مما دعا الكثيرين الى تثمين جهودهم والتأصيل لها، لبيان مدى إلمام التراث العربي بكل ما يبدو معاصرا، والفعل الكلامي هو الانجاز الذي يؤديه المتكلم بمجرد تلفظه بملفوظات معينة، فاللغة ليست وسيلة للتخاطب والتواصل فحسب، إنما هي وسيلة للتأثير في الآخر وتغيير سلوكه ،ونسعى من خلال هذا المقال لإبراز ملامح نظرية أفعال الكلام لدى كل من أوستين وسيرل ومقارنتها بما جاء به العرب من جهود فيما يتعلق بهذه النظرية . Abstract: Those, who follow the books and resources that deals with the pragmatic approach ,find that they are not without a presentation of the principles of verbal acts , because they are considered like a part of pragmatics.What should be mentioned here, it is that all these studies have some original roots in our Arab heritage that is characterized by comprehensiveness and encyclopedia, this fact called many scholars to value these efforts . Their purpose was to show to what extent of the Arab heritage covers all the contemporary issues. Verbal action is the achievement that the speaker performs by simply uttering it in specific words. In the study of language, this is not only a means of discourse and communication, but rather a means of influencing the other and changing his behavious. In this paper , we seek to highlight the features of the theory of speech acts in Austin and Searle's theory and to compare it with the efforts made by the Arabs regarding this theory.
مقال
Keywords: أفعال الكلام ; الأساليب العربية ; الفعل الإنجازي ; التلفظ ; القصد